Computational modelling of protein-protein and cell-cell interaction across multiple scales - Koon, Yen Ling (2018)
To gain a deeper insight into the inner workings of biology, computational modelling is performed for three projects spanning three different scales: namely at the molecular or protein scale, at the intracellular scale and at the intercellular level. 1) The first project is conducted at the molecular or protein level where we have uncovered Chk1 as a novel interactor of POPX2 through our bioinformatics analysis pipeline. Our bioinformatics analysis pipeline is a combination of two separate strategies: 1. Prediction of POPX2 substrates by finding proteins with close phylogeny relation to known substrates of POPX2 and PP2C domain, 2. Prediction of POPX2 substrates by curation of known interactors of proteins sharing homology to POPX2 using STRING database. 2) The second project is performed at the intracellular level. By constructing a reaction-advection-diffusion model, we have found that to achieve optimum signalling efficiency of proteins transported by scaffold proteins and motor proteins, an optimum concentration of scaffold proteins as well as an optimum speed of motor proteins is necessary. 3) The final project investigates the intercellular realm where we explore how differential regulation of angiogenesis leads to different sprouting angiogenesis patterns. Specifically, we conclude that by considering two commonly neglected mechanisms, namely intracellular Notch heterogeneity as well as tension modulation of rate constants, experimentally observed sprouting patterns can be recapitulated.